The impact of organizational capabilities on the international performance of knowledge-based firms - Mitra Samadi; Seyed Reza Mirnezami; Mohammad Torabi Khargh (Journal of Open Innovation: Technology, Market and Complexity, 2023)
This study aims to investigate the capabilities of knowledge-based firms in Iranian chemical industries and to analyze the link between these capabilities and the firms’ international performance in terms of exports. By combining 18 different output-based indicators and also using the analytic hierarchy process (AHP), six measures for technological, manufacturing, R&D, marketing, organizing, and financial capabilities were constructed. Accordingly, the impact of mentioned capabilities on the international performance of knowledge-based firms in the period of 2015–2018 was examined using regression analysis. The results show more or less the same results when we investigate total export in dollar amount and the number of export destinations: R&D, manufacturing, marketing, and financial capabilities are the factors that boost export in the firms. However, when we control the export performance with the number of employees, the results show that marketing capability is the only factor significantly affecting total export per employee. In other words, marketing capability is the only one always identified as the important factor of firms’ exports. This finding implies no “one-size-fits-all” solution for empowering firms to boost exports. Depending on the goals (total export, export per employee, and the number of export destinations), the government should target different sets of organizational capabilities as the support package for firms. The present study can be a basis for the decision-making approach of managers and policymakers to upgrade the capabilities and improve the competitiveness of these firms in the international environment.